Assessing knowledge of Ebola virus among health sciences students and healthcare professionals: a cross-sectional study in Ajman, UAE - Arida, Abdul Karim; Al Jarrad, Ahmad; Alramahi, Mu’ayyad; Ahmad, Waleed; Janoudi, Ahmad; Gopakumar, Aji; Thoppuram, Nithin Koshy; Muttappallymyalil, Jayakumary (International Journal Of Community Medicine And Public Health, 2020)
Background: This study aimed to evaluate the knowledge of Ebola virus infection among students enrolled in health sciences programmes (Medicine, Dentistry and Allied Health Professions) and healthcare professionals in a private hospital in Ajman, UAE. Methods: It was a population based study where no samples collected and sampling technique involved. This cross-sectional study included 719 participants, among which 463 were health sciences students and 256 healthcare professionals. A self-administered questionnaire was given to all participants. A score of 50% or more in the questionnaire was considered a good score, representing a good level of knowledge and practice. Non-parametric statistical tests such as Mann-Whitney U test, Kruskal-Wallis test, and Chi-squared test were applied along with logistic regression model using SPSS version 21. Results: 100% of healthcare professionals (256) and 90.1% of students across all programs (417) were identified as having a good level of knowledge about Ebola virus infection. This observed difference in knowledge between type of participant was found to be statistically significant (p≤0.001). Compared to students, healthcare professionals were 8.9 times more likely to have higher levels of knowledge (score ≥75% in the questionnaire; COR: 8.9, CI: 5.5-14.3, p≤0.001). Higher knowledge identified among students of MBBS program (96.8%), clinical years of study, age ≥20 years old (92.4%), and students from South East Asia. Conclusions: Various factors were found to contribute significantly to participants having good levels of knowledge, including type of participant (healthcare profession vs student), students’ program of study and participants’ region of origin.